Legal protection for aggrieved parties in electronic contracts (e-contracts) - Enjum Jumhana; Harry Qurba (Institute Of computer Science (IOCS), 2026)
The development of information technology has given rise to new forms of transactions through electronic contracts (e-contracts) that offer convenience and efficiency, but also pose potential losses for parties, especially consumers. This study aims to analyze the form of legal protection for parties who are harmed in the implementation of electronic contracts in Indonesia. The research method used is normative juridical with a statutory and conceptual approach, through a study of the Civil Code, Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), and Law Number 8 of 1999 concerning Consumer Protection. The theoretical basis used is the theory of legal protection from Philipus M. Hadjon and the theory of contractual justice according to John Rawls. The results of the study indicate that legal protection for parties who are harmed in electronic contracts can be provided through preventive and repressive mechanisms, including the right to obtain correct information, complaint mechanisms, and dispute resolution through judicial institutions or alternatives such as arbitration and online mediation. This study emphasizes the importance of strengthening regulations and digital literacy so that the principle of good faith and balance of rights in electronic contracts can be effectively guaranteed.